Using the Theory of Planned Behavior to Explore Factors Associated with the Behavior of Consuming Blood Booster Tablets Among Adolescent Girls in Bantul Regency - Retno Heru Setyorini; Era Revika (Universitas Airlangga, 2024)
Background: Providing iron and folic acid through the ingestion of blood booster tablets is an intervention to lower the prevalence of anemia in adolescents. However, just a small percentage of adolescent girls have consumed blood booster tablets as prescribed. Aims: To identify the factors related to the behavior of consuming blood booster tablets among adolescent girls in Bantul Regency based on the Theory of Planned Behavior. Methods: The cross-sectional study was conducted in Bantul Regency, a Special Region of Yogyakarta Province, between March and May 2023. A total of 381 adolescent girls aged 16-18 years participated in filling out questionnaires to collect data. The questionnaire includes socio-demographics, knowledge about blood booster tablets and anemia, attitudes, subjective norms, intentions, and behaviors of consuming blood booster tablets. Path Analysis was used to analyze the data with statistical significance (p) at 0.05. Result: As a result, intention directly influences the behavior of consuming blood booster tablets (p=˂0.001). Subjective norms have a direct influence on the behavior of consuming blood booster tablets (p=0.023) and have an indirect influence through attitudes (p˂0.001) and intentions (p˂0.001). Attitude has an indirect influence on the behavior of consuming blood booster tablets through intention (˂0.001), then the level of knowledge has an indirect influence on intention (p=0.037) and attitude (p=0.032). Conclusion: Adolescent girls will have good consumption behavior of blood booster tablets if they have a positive attitude, a high level of knowledge, subjective norms, and high intentions. These findings can be used to design health promotion models useful for increasing the consumption behavior of blood booster tablets. Further research is needed to find the right educational model to increase knowledge, attitudes, subjective norms, and intentions to consume blood booster tablets.